Unveiling Shades of Green Food beyond Labels. Evidence from an Online Experiment to Climate Adaptation - Cecilia Castaldo; Matilde Giaccherini; Giacomo Pallante; Alessandro Palma (CESifo GmbH, 2024)
We investigate the role of information strategy in shifting the purchasing preferences of “green” organic consumers towards a subset of “greener” products that foster adaptation to climate change. We focus on organic pasta, a widely consumed food, to conduct field experiment that involves consumers purchasing on the on-line shop of an Italian organic brand leader. Participants received one of two informational messages about an ancient durum wheat cultivar, renowned for its drought tolerance compared to modern durum wheat. The colloquial message results in 13% increase in the market share of “greener” pasta, despite its price premium. Conversely, the science-based message is effective only among consumers who prioritize environmental sustainability in their organic food purchases and rely on scientific information in their daily lives. Overall effects persist for at least three months and are more pronounced among women, young individuals, and those with higher levels of education. Potential moral licensing is detected among the “greenest” consumers who were already highly engaged.
Keywords: C93; Q57; D12; 330; field experiment; consumers; information; organic food; climate change adaptation